Cornea Donation in Organ Donors: Recommendations to Increase Acceptance. (August 2017) - Rennesson, C.; Moretti, D.; Arnaud, E.; Brousoz, S.; Flatres, S.; Freitas, C.; Hechinger, S.; Simon, J.; Gasche, Y.
Abstract : Introduction: In our programme, cornea donation is usually requested to relatives the day following death. In the case of a potential organ donor, consent for tissue donation and specifically for corneas is evoked at the same time as organ donation. The family and the intensive care physician must validate together the organs and tissues the patient wished to donate or not. We analysed the rate of refusal for cornea donation in all interviews for potential organ donors. Methods: Retrospective study from April 2013 to December 2016, in the Geneva University Hospitals included 56 potential organ donors for which the relatives expressed the patients' consent to organ donation; among these patients there were two categories: donation after brain death (DBD) and donation after cardiac death (DCD). Results: During the study period the refusal rate in our hospital for organ donation was 46%; very similar to the overall refusal rate for cornea only donation of 47%. An explanation can be the global reticence for ocular retrieval in the population, even though we only request corneal tissue. We have observed a marked difference between refusal rates for cornea donation depending on type of organ donors; in DBD the refusal rate is 32% versus 22% for DCD. We suspect this could be due to the fact that different teams are involved in consent seeking. In DBD, the interview is led by the intensive care physician and then followed up by a procurement-transplant coordinator. For DCD, it is the Specialised Nurses for Organ Donation(SNOD) who meets with the relatives and determines with them, the patients' presumed wishes, including precisions on which organs and tissues can be considered for donation. The SNOD's have advanced training in communication skills, including understanding the behaviour of families during the interview. Conclusion: In order to increase the consent rate for cornea donation in potential organ donors, requesting by SNOD's seems to be an efficient method. This should be coupled with the development of information campaigns concerning organ and tissue donation with a particular emphasis on cornea donation.